A novel μ-conotoxin from worm-hunting Conus tessulatus that selectively inhibit rat TTX-resistant sodium currents. (May 2017) - Yang, Manyi; Zhao, Shuang; Min, Xiaoli; Shao, Meiying; Chen, Yongheng; Chen, Zhuchu; Zhou, Maojun
Abstract: μ-conotoxins are a group of marine Conus peptides that inhibit sodium currents, so μ-conotoxins are valuable in sodium channel research and new analgesic drug discovery. Here, a novel μ-conotoxin TsIIIA was identified from a worm-hunting Conus tessulatus. TsIIIA was chemical synthesized according to its amino acid sequence GCCRWPCPSRCGMARCCSS and identified by mass spectrum. Patch clamp on rat dorsal root ganglion cells showed that 10 μM TsIIIA specifically inhibit TTX-resistant sodium currents but has no effect on TTX-sensitive sodium currents. TsIIIA inhibits TTX-resistant sodium currents by a dose-dependent mode with an IC50 of 2.61 μM. Further study showed 10 μM TsIIIA has no obvious effect on the current-voltage relationships, conductance-voltage relationships and voltage-dependence of steady-state inactivation of TTX-resistant sodium channels. Mice hotplate analgesic assay indicated that TsIIIA obviously increase the pain threshold at 0.5–4 h. In addition, TsIIIA has better analgesic effects than Ziconotide, indicating that TsIIIA was a valuable lead compound for development of new analgesic drug. Highlights: We identified a vermivorous u-conotoxin TsIIIA from Conus tessulatus. TsIIIA inhibits TTX-resistant sodium currents by a dose-dependent mode with an IC50 of 2.61 uM. Mice hotplate analgesic assay indicated that TsIIIA has better analgesic effects than Ziconotide.